Derivation of new human embryonic stem cell lines (Yazd1-3) and their vitrification using Cryotech and Cryowin tools: A lab resources report - Fatemeh Akyash; Somayyeh Sadat Tahajjodi; Ehsan Farashahi Yazd; Fatemeh Hajizadeh-Tafti; Fatemeh Sadeghian-Nodoushan; Jalal Golzadeh; Hassan Heidarian Meimandi; Harry Moore; Behrouz Aflatoonian (Shahid Sadoughi University of Medical Sciences, 2019)
Background Cell banking of initial outgrowths from newly derived human embryonic stem cells (hESCs) requires an efficient freezing method. Vitrification is used for the preservation of gametes and early embryos in assisted reproduction techniques (ART). Moreover, vitrification was applied for cryopreservation of hESCs using open pulled straws. Objective To derive and characterize new hESC lines and then use Cryotech and Cryowin tools for their vitrification. Materials and Methods Human ESC lines were generated in a microdrop culture system using mouse embryonic fibroblasts (MEFs) as the feeder layer; this was later scaled up using both MEFs and Yazd human foreskin fibroblasts batch 8 (YhFF#8). To bank the cell lines, master cell banks of 100 Cryotech and Cryowin tools were produced for each individual cell line using the vitrification method; flasks of hESC lines were also cryopreserved using a conventional slow-freezing method. Results The pluripotency of cell lines was assessed by their expression of pluripotency-associated genes (OCT4/POU5F1, NANOG, and SOX2) and markers such as SSEA4, TRA-1-60, and TRA-2-49. Their in vitro capacity to differentiate into germ layers and germ cells using embryoid body (EB) formation and monolayer culture was assessed by screening the expression of differentiation-associated genes. The chromosomal constitution of each hESC line was assessed by G-banding karyotyping. Conclusion Cryotech and Cryowin tools used to vitrify new hESCs at an early stage of derivation is an efficient method of preserving hESCs.